45.2k views
5 votes
I would appreciate it if someone would quickly help me solve this problem:

6x = 5x -
(3)/(4)

User Domsom
by
5.8k points

2 Answers

4 votes

Answer:

6x = 5x - 3/4

6x - 5x = -3/4

x = -3/4


User Scott Davidson
by
5.2k points
4 votes

Answer:

x = - 3/4

Explanation:

I think you might be overthinking the problem. Anyone who can set up latex can't be fooled for long.

Just subtract 5x from both sides.

6x - 5x = 5x - 5x - (3/4)

x = - 3/4

User Claes
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.